PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KERJASAMA TIM DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN WARUNG MINA CABANG RENON - Puryatini Putri, Luh De; Sariyathi, Ni Ketut (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
ABSTRACT Employee performance is how much employees contribute to the organization that is the quantity, quality, duration and output attendance absenteeism at the workplace and cooperative attitude. Employees were able to give a good performance for the company, when the company needs to consider all the factors that affect employee performance. This study aimed to analyze the effect of transformational leadership, teamwork and communication to employees performance at Warung Mina Branch Renon, Denpasar. This study uses the entire population as respondents as many as 55 people were listed as employees of Warung Mina Branch Renon. Data were collected through observation, interviews and questionnaires. The analysis technique used is the technique of multiple linear regression analysis. Hypothesis testing results show that all the proposed hypothesis is accepted. Transformational leadership and significant positive effect on employee performance. Kerjama team positive and significant effect on employee performance. Communications positive and significant effect on employee performance.
Keywords: transformational leadership, teamwork, communication, employee performance